2006
DOI: 10.1007/s10164-006-0006-z
|View full text |Cite
|
Sign up to set email alerts
|

Sexual selection in genetic colour-polymorphic species: a review of experimental studies and perspectives

Abstract: Sexual selection theory has primarily focussed on the role of mating preferences for the best individuals in the evolution of condition-dependent ornaments, traits that signal absolute quality. Because the most suitable mate for one individual is not always the best for others, however, we argue that nondirectional mate choice can promote the evolution of alternative morphs that are not condition-dependent in their expression (i.e. genetic polymorphism). We list the different mate-choice rules (i.e. all indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 70 publications
2
59
0
Order By: Relevance
“…Here, we combine information from a mating experiment with published estimates of survival selection in order to examine their interaction and the potential role of frequency‐dependent selection on the maintenance of colour polymorphism in an aposematic organism. The results aim to confirm an idea previously expressed by Roulin & Bize (): it is difficult to explain polymorphisms if the common morph derives a mating advantage, but in a spatially structured population, some degree of gene flow could potentially counteract the predicted loss of genetic variation. Interestingly, a modelling study of a particular colour polymorphism – Müllerian mimicry – shows that too high gene flow can again break down a polymorphism, because the system then effectively behaves like one unit with averaged parameter values (Joron & Iwasa ).…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Here, we combine information from a mating experiment with published estimates of survival selection in order to examine their interaction and the potential role of frequency‐dependent selection on the maintenance of colour polymorphism in an aposematic organism. The results aim to confirm an idea previously expressed by Roulin & Bize (): it is difficult to explain polymorphisms if the common morph derives a mating advantage, but in a spatially structured population, some degree of gene flow could potentially counteract the predicted loss of genetic variation. Interestingly, a modelling study of a particular colour polymorphism – Müllerian mimicry – shows that too high gene flow can again break down a polymorphism, because the system then effectively behaves like one unit with averaged parameter values (Joron & Iwasa ).…”
Section: Introductionsupporting
confidence: 77%
“…predator/parasitic community or vegetation structure) and the level of gene flow can determine whether either one of the morphs spreads to fixation in a population, or whether the selective mosaic maintains a polymorphism indefinitely. If we assume that the yellow male survival advantage is not fixed but varies spatially – as our extensive natural sampling suggests – our results add a quantitative component to the ideas expressed by Roulin & Bize () and Calsbeek, Bonvini & Cox (). More specifically, we show that both low and quite strong gene flow between sites forming the selection mosaic can keep the polymorphism intact.…”
Section: Discussionsupporting
confidence: 55%
“…From an ultimate point of view, the finding that immune responsiveness correlates with female plumage coloration in the tawny owl may suggest that melanin‐based colours have an adaptive function in sexual selection, assuming that individuals can detect variation in coloration in conspecifics (Hamilton & Zuk 1982; Roulin & Bize 2007). Indeed, it has recently been shown that visual cues can be used by nocturnal birds during mate choice (Roulin 1999; Penteriani et al .…”
Section: Discussionmentioning
confidence: 99%
“…One factor maintaining such polymorphism is disassortative mating (Roulin 2004;Roulin & Bize 2007), in which reproductive pairings between different phenotypes are more common than expected by chance. Recently, there has been a focus on disassortative mating as a mechanism for increasing the frequency of heterozygote at a certain locus, which has the positive effects over the homozygote, and/or inbreeding avoidance (Jordan & Bruford 1998;Penn & Potts 1999;Tregenza & Wedell 2000;Penn 2002;Mays & Hill 2004).…”
Section: Introductionmentioning
confidence: 99%